Pengembangan Pengetahuan Agama Islam Anak melalui Kegiatan Pesantren di Pondok Roudhotul Ilmi Dusun Kadisono Desa Klangonan Kebomas Gresik - Rahma Nur Fadhilah (Center of Education Journal (CEJou), 2021)
This study aims to explain the various types of Islamic boarding school activities that are applied and the development of children's Islamic religious knowledge through these activities. This study uses a qualitative approach to the type of phenomenological research. Data mining in this study used in-depth interviews. As a boarding school that was just established in 2014 and is still in the process of starting from scratch, the Roudhotul Ilmi Islamic boarding school has an effort to develop children's knowledge through pesantren activities. Of course, this is the first thing to be done in the Kadisono Hamlet with the aim of producing children who are knowledgeable and aretiqomah in carrying out their obligations as Muslims. From the results of the study it was found that there were various kinds of activities carried out, namely: congregational prayers, education of the Qur'an, marhabanan, istighosah, rotibul hadad, manqib, diniyah. All of the above activities are carried out routinely according to the schedule that has been applied. The implementation of these activities can be a way for caregivers and parents to develop their children's Islamic religious knowledge